Protective effect of polyphenol-rich extract prepared from Malaysian cocoa (Theobroma cacao) on glucose levels and lipid profiles in streptozotocin-induced diabetic rats - Mohd Mokhtar, Ruzaidi Azli; Mhd Jalil, Abbe Maleyki; Ismail, Amin; Abdul Ghani, Nawalyah; Hamid, Muhajir (Society of Chemical Industry, 2008)
BACKGROUND: Cocoa beans are used for preparing cocoa liquor and cocoa powder, which are the main ingredients of cocoa-based products. Previous studies have reported the health benefits of cocoa polyphenols in reducing the risk of cardiovascular diseases. However, there is no report on the efficacy of cocoa polyphenols on diabetes mellitus. Therefore this study was designed to evaluate the protective effect of cocoa polyphenol-rich extract (CE) on glucose levels and lipid profiles in streptozotocin (STZ)-induced diabetic rats. Male Sprague-Dawley rats were divided into diabetic control, diabetic CE and diabetic glibenclamide groups.